Changes in quality of life, cognition and functional status following catheter ablation of atrial fibrillation. Issue 24 (12th October 2020) - Piccini, Jonathan P; Todd, Derick M; Massaro, Tyler; Lougee, Aimee; Haeusler, Karl Georg; Blank, Benjamin; de Bono, Joseph Paul; Callans, David J; Elvan, Arif; Fetsch, Thomas; Van Gelder, Isabelle; Gentlesk, Philip; et al.
Abstract : Objective: To investigate changes in quality of life (QoL), cognition and functional status according to arrhythmia recurrence after atrial fibrillation (AF) ablation. Methods: We compared QoL, cognition and functional status in patients with recurrent atrial tachycardia (AT)/AF versus those without recurrent AT/AF in the AXAFA–AFNET 5 clinical trial. We also sought to identify factors associated with improvement in QoL and functional status following AF ablation by overall change scores with and without analysis of covariance (ANCOVA). Results: Among 518 patients who underwent AF ablation, 154 (29.7%) experienced recurrent AT/AF at 3 months. Patients with recurrent AT/AF had higher mean CHA2 DS2 -VASc scores (2.8 vs 2.3, p<0.001) and more persistent forms of AF (51 vs 39%, p=0.012). Median changes in the SF-12 physical (3 (25th, 75th: −1, 8) vs 1 (−5, 8), p=0.026) and mental scores (2 (−3, 9) vs 0 (−4, 5), p=0.004), EQ-5D (0 (0, 2) vs 0 (−0.1, 0.1), p=0.027) and Karnofsky functional status scores (10 (0, 10) vs 0 (0, 10), p=0.001) were more favourable in patients without recurrent AT/AF. In the overall cohort, the proportion with at least mild cognitive impairment (Montreal Cognitive Assessment <26) declined from 30.3% (n=157) at baseline to 21.8% (n=113) at follow-up. ANCOVA identified greater improvement in Karnofsky functional status (p<0.001) but not SF-12 physical (p=0.238) or mental scores (p=0.065) in those without recurrent AT/AF compared with patients with recurrent AT/AF. Conclusions: Patients without recurrent AT/AF appear to experience greater improvement in functional status but similar QoL as those with recurrent AT/AF after AF ablation.